When a Hug Helps: Reducing Emotional Outbursts in Children with Autism - Rodhiyah, Raychana Robbi; Nasywa Salsabila Khairunnisa; Maulina Ratih Kusuma Wardani; Imron Maulana Aziz; Ulimaz Ika Rahmawati; Tri Rejeki Andayani (Universitas Islam Negeri Raden Intan Lampung, 2023)
Management of temper tantrums in children with autism can be approached in various ways. A review of the literature indicates four effective approaches for addressing temper tantrums in autistic children: physiological, cognitive, interactional, and spiritual approaches. The physiological approach, in the form of hugging, has been shown to help manage temper tantrums. Furthermore, in relation to emotional regulation, an Islamic teaching suggests that changes in body position can help regulate anger. This study aims to examine the effect of hugging combined with body position adjustment on reducing temper tantrums in children with autism. The research employed a quasi-experimental one-group pretest-posttest design. Five autistic children without comorbidities, aged 7–13 years, were selected through purposive non-random sampling. Data were collected using a temper tantrum questionnaire filled out by the subjects’ parents and analyzed using the Wilcoxon Signed Rank Test. The analysis results showed a significant decrease in the posttest temper tantrum mean compared to the pretest mean (with negative ranks exceeding positive ranks and a significance level of 0.007 or p < 0.05). Likewise, a significant difference was found between the pretest and follow-up means (p = 0.002 or p < 0.05). These findings indicate that the intervention of hugging combined with body position adjustment effectively reduces temper tantrums in children with autism. Keywords : Temper Tantrum, Intervention for children with autism, embrace, Body positioning atau body posture adjustment